Transitioning to Quality Education - Jeronen, Eila (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
Transitioning to Quality Education focuses on the fourth UN Sustainable Development Goal. According to SDG 4, every learner should acquire the knowledge and skills needed to promote sustainable development (UN 2015, 17). Thus, the aim of sustainability education is to foster learners to be creative and responsible global citizens, who critically reflect on the ideas of sustainable development and the values that underlie them, and take responsible actions for sustainable development (UNESCO 2017). Sustainability is strongly connected to attitudes and values, therefore, applications of sustainability are complicated. Quality education requires teachers to have competences, knowledge, and skills to be able to plan and carry out meaningful education and teaching in sustainability. The aim of Transitioning to Quality Education is to provide versatile experiences and new knowledge on the cognitive, affective, and social issues that are important for promoting sustainable development in formal and non-formal education. Transitioning to Quality Education is part of MDPI's new Open Access book series Transitioning to Sustainability. With this series, MDPI pursues environmentally and socially relevant research which contributes to efforts toward a sustainable world. Transitioning to Sustainability aims to add to the conversation about regional and global sustainable development according to the 17 SDGs. Set to be published in 2020/2021, the book series is intended to reach beyond disciplinary, even academic boundaries.